Available but Uncontested: Why Budget Transparency Stops Short of Accountability in Schools - Supatmin Supatmin; Hestu Nugroho Warasto (JUMPA : Jurnal Manajemen Pendidikan, 2026)
Budget transparency has become the standard prescription for improving governance in education finance, yet little is known about what happens once the policy reaches an individual school. This study examines how key actors experience and enact education budget transparency in senior high schools through a transcendental phenomenological design. Fourteen participants took part. They comprised principals, treasurers, school committee chairs, and provincial officials. In-depth interviews, twelve field observations, and analysis of school financial documents supplied the data, which were then interpreted using the five analytical stages of Moustakas. Five themes emerged. Transparency fragmented on entry into the school, and actors rebuilt it variously as legal obligation, moral trusteeship, and managerial instrument. Practices diverged along two independent axes. Infrastructure governed whether financial information became available, while committee dynamics governed whether anyone questioned it. Obstacles accumulated in three layers of unequal tractability, and the patron authority above principals in parts of the foundation sector lay beyond the reach of educational administration. Schools improvised effective remedies that stayed unauthorized and personally sustained. Consequences cut both ways, because trust and financial discipline improved while managerial attention drifted away from teaching. An availability-contestation model follows from these findings and separates disclosure from answerability. The policy implication is direct. Investment in reporting platforms moves a school along one axis only, and accountability instead demands stronger deliberative capacity in school committees rather than a larger volume of disclosure.